Optimasi Inventori Dengan Pendekatan Deterministik Dinamis Pada Industri Manufaktur Roti - Yevita Nursyanti; Karina Shalsabila (OPSI, 2020)
This research is to optimize the inventory of bakery products by using several approaches to dynamic deterministic methods. Dynamic deterministic methods used in this research are Wagner-Whitin Algorithm, Silver Meal, Least Unit Cost, Economic Part Period, Lot for Lot, Total Cost Least, Period Order Quantity and Part Period Balancing. The best method is the method that produces the lowest total inventory cost. The result of calculating the total inventory cost using the Wagner-Whitin  Algorithm method is Rp. 2,006,592 ,. The SilverMeal method generates a total inventory cost of Rp. 2,043,725.49. The Least Unit Cost method generates a total inventory cost of Rp. 1,894,624.18. The Economic Part Period method produces a total inventory cost of Rp. 1,235,546.41. The Lot for Lot method generates a total inventory cost of Rp. 2,835,000.00. The Least Total Cost method generates a total inventory cost of Rp. 1,894,624.18. The Period Order Quantity method generates a total inventory cost of Rp. 2,750,767.97. The Part Period Balancing method generates a total inventory cost of Rp. 1,894,624. From the results of all methods, the best method that can be made a proposal to UD.Roti Isabela is the Economic Part Period method with a policy of ordering 3 times an order with a total inventory cost of Rp 1,235,546.41.